Peningkatan Prestasi Santri Dalam Public Speaking Melalui Pembinaan Kegiatan Muhadharah - Putri, Zahra Amalia; Aliyudin, Mukhlis; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The purpose of this study was to determine the improvement of cognitive, affective and behavioral aspects of students after participating in muhadharah activities in improving student achievement in public speaking. This research uses phenomenological methods with an interpretive paradigm. The results showed that: (1) Cognitive aspects of students; Coaching muhadharah activities as a routine activity for developing students' public speaking potential. (2) Affective aspects of students; Student motivation as an affective support for public speaking achievements. (3) Behavioral aspects of students; Strengthening mentality as a positive impact in the process of self-development of students. The results of this study can be used as additional information for students who are conducting similar research.